Population structure of indigenous chicken (Gallus gallus domesticus) from the east coast of peninsular Malaysia inferred using mitochondrial DNA control religion - Mustapha Jamilu Adamu
Indigenous chicken production has been a source of income among rural families since centuries ago. Their characteristics such as resilience to disease and hardiness in harsh local weather, as well as high market demand have made them an immediate source of income and protein to the rural community. Indigenous chicken production involves keeping the bird at home backyard. However, their production is given less consideration compared with the commercial broilers due to their slow growth rate, low feed conversion efficiency, and few eggs production per year. To improve them through selection and cross-breeding program, their population structure has to be clarified. However, there is insufficient information concerning their population structure. Poultry production including the indigenous chicken is one of the livestock production projects under current Malaysian government policy, the East Coast Economic Region (ECER). This policy was introduced in 2008 in order to sustain the agricultural industry, provide employment opportunities and increase the monthly income among the participants in the region. This study was aimed to provide the baseline data on the fundamental population genetics of the indigenous chicken in order to determine how to protect and exploit these natural gene resources. A total of 59 chicken samples were collected from Kelantan, Terengganu and Pahang. The sampling locations that are close to one another were pooled together and considered as one population. The 600 bp length sequence of partial mtDNA control region was amplified, sequenced and aligned. Only 546 bp were used for the sequence data analyses. The remaining sequence located outside of the control region was removed. Eleven haplotypes (Hap) and 23 polymorphic sites were detected among all the samples. Hap-I, Hap-4 and Hap-6 were revealed as common haplotypes to all populations. Hap-l was the most widespread haplotype among the three populations and it comprised of 45.8% of the total samples. The average haplotype diversity and nucleotide diversity were 0.7633 and 0.00818, respectively. Non-significant values of Tajima's D and Fu's Fs were obtained in Pahang and Terengganu, indicating that they are in genetic equilibrium. Kelantan showed significant deviation from neutrality (P<0.05), indicating population expansion. The haplotype neighbour joining dendrogram revealed shallow topology and no significant genealogical clusters of samples corresponding to sampling locations was observed. Analysis of molecular variance (AMOVA) showed significant differences among the populations (Fst = O. 0.08175, P<0.05). In pairwise comparison of the samples, significant population genetic differentiation (P<0.05) was observed only in Kelantan population, indicating the genetic heterogeneity. This signifies that, indigenous chicken in Kelantan may be genetically differentiated population as compared to Pahang and Terengganu. Meanwhile, the non-significant FST value indicated that Pahang and Terengganu were genetically related populations. In order to reveal more genetic variation of these populations, further study using broad sampling location, larger sample sizes and longer mtDNA fragment is recommended. Conservation initiatives on Kelantan population should be carried out to prevent the loss of these natural gene resources, which are valuable for future broodstock selection and cross-breeding program.